PENGARUH CAPITAL ADEQUACY RATIO (CAR), FINANCING TO DEPOSIT RATIO (FDR), UKURAN DIREKSI, UKURAN DEWAN PENGAWAS SYARIAH, DAN UKURAN BANK TERHADAP RETURN ON DEPOSIT (ROD) PADA BANK UMUM SYARIAH DI INDONESIA DENGAN KEPEMILIKAN ASING SEBAGAI VARIABEL DUMMY - Nofendi, Deki; Wahyudi, Sugeng (Diponegoro Journal of Management, 2017)
Return on Deposit (ROD) is one of profitability measures in syaria bank. The purpose of this paper is to analyze determinants of Return on Deposit (ROD)   of syaria bank in Indonesia. Those determinant factors are Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), board size, Shari’a Supervisory Board size, bank size, market interest rate, and foreign ownership. The sample in this study consisted of 11 syari’a banks from year periode of 2011 until 2015. The sample was selected by purposive sampling method. The research hypothesis testing method of this paper uses multiple regression analysis. The results show that Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Shari’a Supervisory Board size  significantly influence Return on Deposit (ROD) in positive way. However, the results do not show any relationship between board size and  Return on Deposit (ROD) neither do banks’ size and Return on Deposit (ROD). Domestic sharia bank has better ROD’s performance than foreign sharia bank.